Pembelajaran Fisika Dengan Model PBL Berbasis STEM Untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik SMA - Firdausi Nuzula; Budi Jatmiko (Student Scientific Creativity Journal, 2023)
Critical thinking is one of the skills that is needed in today's digital era because in the future students are required to have a way of thinking that is more sensitive to diversity. Thus, the purpose of this research is to identify in depth the effect of STEM-based PBL learning model on critical thinking skills through literature study. This research uses the literature review method and bibliographic analysis. In the literature review method, collecting information which was then reduced until three samples of articles were reviewed. In bibliography analysis, collecting data with the help of Publish or Perish software with many 199 articles, in ris file format, and then visualized by VOSviewer. The results showed that the STEM-based PBL model was able to improve the critical thinking skills of high school students.